Multimorbidity: The Brazilian Longitudinal Study of Aging (ELSI-Brazil) - Nunes, Bruno Pereira; Batista, Sandro Rogério Rodrigues; Andrade, Fabíola Bof de; Souza Junior, Paulo Roberto Borges de; Lima-Costa, Maria Fernanda; Facchini, Luiz Augusto (Revista de saúde pública, 2018)
To evaluate the occurrence and factors associated with multimorbidity among Brazilians aged 50 years and over. This is a cross-sectional study in a nation-based cohort of the non-institutionalized population in Brazil. Data were collected between 2015 and 2016. Multimorbidity was assessed from a list of 19 morbidities, which were categorized into ≥ 2 and ≥ 3 diseases. The analysis included the calculation of frequencies and the most frequent 10 pairs and triplets of combinations of diseases. The crude and adjusted analyses evaluated the demographic, socioeconomic, behavioral, and contextual variables (area of residence, geopolitical region, and coverage of the Family Health Strategy) using Poisson regression. From the total of 9,412 individuals, 67.8% (95%CI 65.6-69.9) and 47.1% (95%CI 44.8-49.4) showed ≥ 2 and ≥ 3 diseases, respectively. In the adjusted analysis, women, older persons, and those who did not consume alcohol had increased multimorbidity. There were no associations with race, area of residence, geopolitical region, and coverage of the Family Health Strategy. The 10 pairs (frequencies observed between 11.6% and 23.2%) and the 10 triplets (frequencies observed between 4.9% and 9.5%) of the most frequent diseases mostly included back problems (15 times) and systemic arterial hypertension (11 times). All combinations were statistically higher than expected by chance. The occurrence of multimorbidity was high even among younger individuals (50 to 59 years). Approximately two in three (≥ 2 diseases) and one in two (≥ 3 diseases) individuals aged 50 years and over presented multimorbidity, which represents 26 and 18 million persons in Brazil, respectively. We observed high frequencies of combinations of morbidities.